Atorvastatin calcium loaded chitosan nanoparticles: in vitro evaluation and in vivo pharmacokinetic studies in rabbits - Abdul Baquee Ahmed; Ranjit Konwar; Rupa Sengupta (Universidade de São Paulo, 2015)
In this study, we prepared atorvastatin calcium (AVST) loaded chitosan nanoparticles to improve the oral bioavailability of the drug. Nanoparticles were prepared by solvent evaporation technique and evaluated for its particle size, entrapment efficiency, zeta potential, in vitro release and surface morphology by scanning electron microscopy (SEM). In addition, the pharmacokinetics of AVST from the optimized formulation (FT5) was compared with marketed immediate release formulation (Atorva(r)) in rabbits. Particle size of prepared nanoparticles was ranged between 179.3 ± 7.12 to 256.8 ± 8.24 nm with a low polydispersity index (PI) value. Zeta potential study showed that the particles are stable with positive values between 13.03 ± 0.32 to 46.90 ± 0.49 mV. FT-IR studies confirmed the absence of incompatibility of AVST with excipient used in the formulations. In vitro release study showed that the drug release was sustained for 48 h. Results of pharmacokinetics study showed significant changes in the pharmacokinetic parameter (2.2 fold increase in AUC) of the optimized formulation as compared to marketed formulation (Atorva(r)). Thus, the developed nanoparticles evidenced the improvement of oral bioavailability of AVST in rabbit model.